State of the immune system in women using the “Provag” probiotic - V. A. Kozlov; A. G. Borisov; A. A. Savchenko; A. E. Kondakov; I. V. Kudryavtsev (Медицинская иммунология)
Lactobacilli are  widely used  in clinical  practice as probiotics, biologically  active  additives  and probiotic products for functional nutrition. Some  probiotics can  be considered as bacterial vaccines  due  to induction of immune response, accompanied by production of specific antibodies. The aim of the present study was to evaluate  the state of cellular and humoral immunity in women  by using probiotic strains of lactobacilli. The  study  included 31 healthy  women  aged  25-45  years.  As a source  of probiotic lactobacterial complex, we used  the  “Provag” preparation (RU  77.99.11.003.E.003746.02.11 of 11.02.2011, 1 capsule  contains 109 Lactobacillus  gasseri 57C,  Lactobacillus  fermentum  57A и Lactobacillus  plantarum  57B).  The  drug  was used for 30 days, at a rate  of one  capsule  per day. The  immune system was examined twice: before  administering the drug and after 30 days of treatment. The study of blood  lymphocyte populations and subpopulations was performed by flow cytometry using direct immunofluorescence technique. The concentration of IgA, IgM, IgG in blood serum was determined using enzyme  immunoassay. To determine specific antibodies, we used passive hemagglutination reaction with erythrocyte diagnosticum. The complex of probiotic lactobacilli Lactobacillus gasseri, Lactobacillus  fermentum  and  Lactobacillus  plantarum corresponding to the “Provag” preparation was used as a source  of antigen. It has been revealed  that  the number of T and B lymphocytes in peripheral blood increased after  30 days  of treatment with  the  probiotic preparation “Provag” in  healthy  women. Elevated contents of T cells was due to the T helper  cell fraction. Increased levels of T helpers and B lymphocytes were associated with stimulation of humoral immunity, as evidenced by increasing concentration of IgA and  IgG in blood  serum.  By means  of passive hemagglutination reaction, we have found  that  90% of healthy  women showed increased concentrations of specific IgA in blood after 30 days of treatment with “Provag” preparation.